Selective and Green Sulfoxidation in Water using a New Chitosan Supported Mo(VI) Complex as Heterogeneous Catalyst. Issue 44 (28th November 2018) - Ahmed, Kabirun; Saikia, Gangutri; Begum, Pakiza; Gogoi, Sandhya Rani; Sharma, Mitu; Talukdar, Hiya; Islam, Nashreen S.
Abstract: Immobilization of oxo‐peroxo molybdenum(VI) species on natural biopolymer, chitosan led to the development of a new heterogeneous catalyst which displayed excellent activity, stability and chemoselectivity for the oxidation of a wide variety of sulfides to the respective sulfoxides by H2 O2 in water, at ambient temperature. The catalyst has been comprehensively characterized by elemental analysis, spectral studies (FTIR, Raman, solid‐state 13 C NMR and diffuse reflectance UV‐Vis), PXRD, Brunauer‐Emmett‐Teller (BET), SEM, EDX and TGA‐DTG analysis. The density functional theory (DFT) method has been employed to study the structure of the synthesized chitosan peroxomolybdenum complex (PMoCh ). In addition to water, the catalyst is also highly compatible with a variety of safer organic solvents like methanol and acetonitrile. Apart from being high yielding and operationally simple, the developed catalytic protocol is environmentally clean and safe as it is absolutely free from halogenated organic solvent. Other significant green attributes of the methodology include its ready scalability, high H2 O2 efficiency and easy recyclability of the catalyst for several catalytic cycles with consistent activity/selectivity profile. Abstract : A heterogeneous water‐compatible and recyclable catalyst has been developed by immobilizing peroxomolybdate on natural biopolymer, chitosan for chemoselective and ecologically sustainable oxidation of sulfides to high purity sulfoxide in aqueous medium at room temperature. The oxidation protocol is high yielding, straightforward and halogen‐free.